Effectiveness of Homoeopathy in Lumpy Skin Disease – A Review of Experimental Evidence (Homoeopathy for All, 2023)
Background : The lumpy skin  disease virus (LSDV), which is a  member of the genus Capripoxvirus  of the family Poxviridae, causes  lumpy skin disease (LSD), a viral  ailment. Cattle and water buffalo  are affected by this transboundary  illness, which is significant  economically. Due to its fast spread  and significant economic losses,  World Organization For Animal  Health (WOAH) added LSD in list  of diseases that require notification.  After seeing outbreaks in Jaipur[8][9]  we conducted a study at Gaushala  in Jaipur, Rajasthan and found  positive results after homoeopathic  medication. Methods: This article reviews  a study that was carried out at  Gaushala in Jaipur (Rajasthan),  in which 200 cattle with lumpy  skin disease were treated with four  homoeopathic drugs i.e. Pulsatiila,  Mer sol, Kali iod, and Silicea to  determine the effectiveness of  Results: The study was conducted  on 200 cattles, out of which 75%  (150) get relief from Merc sol, 14%  (28) from Silicea, 6% (12) from  Pulsatilla, 5% (10) from kali iod.  Conclusion : The study concludes  that homoeopathic medicines have  potential in treatment of lumpy  disease. As the study is conducted  on one place so further such studies  are needed.
Keywords: LSDV; LSD; WOAH; Homoeopathy; Lumpy skin disease